A highly efficient and recyclable Pd(PPh3)4/PEG-400 system for Stille cross-coupling reactions of organostannanes with aryl bromides. (1st September 2017) - Huang, Xue; Yao, Fang; Wei, Ting; Cai, Mingzhong
Pd(PPh3)4 in PEG-400 is shown to be a highly efficient catalyst for the Stille cross-coupling reactions of various organotin compounds with aryl bromides. The reaction could be conducted at 80 °C using NaOAc as base, yielding a variety of biaryls, alkynes and alkenes in good to excellent yields. The isolation of the products was readily performed by extraction with petroleum ether and the Pd(PPh3)4/PEG-400 system could be easily recycled and reused five times without any significant loss of activity.